Improvement in Obstructive Sleep Apnea Diagnosis and Management Wait Times: A Retrospective Analysis of a Home Management Pathway for Obstructive Sleep Apnea - Samuel Alan Stewart; Robert Skomro; John Reid; Erika Penz; Mark Fenton; John Gjevre; David Cotton (Canadian Respiratory Journal)
Obstructive sleep apnea is a common condition within the Canadian population. The current gold standard for diagnosis and management of patients is in-laboratory (in-lab) polysomnography; however, the limited availability of testing options for patients has led to long wait times and increased disease burden within the population. The Sleep Research Laboratory in Saskatoon (Saskatchewan) implemented a home management program to run in parallel with the in-lab system several years ago in an effort to increase their capacity and reduce wait times. The present study was a retrospective analysis of all patients referred to the program between 2009 and 2012. The home management system has improved wait times by diagnosing and managing up to one-half of the referred patient population, reducing the wait for in-lab treatment from a median of 152 days in 2009 to 92 days in 2012 (P<0.0001). Moving forward, home management can provide a viable alternative to in-lab testing for patients who meet strict entry criteria, reducing the in-lab workload and, ultimately, reducing wait times.